The Basilar Artery Collateral Simplified Score: a Novel Collateral Circulation Score Associated With Outcomes in Patients With Basilar Artery Occlusion: Results From the ATTENTION Study - Cong Luo; Rui Li; Chunrong Tao; Ming Cai; Lang Chen; Peng Hao; Xinfeng Liu; Wei Hu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The aim of the current study was to develop a simplified collateral score for basilar artery occlusion and assess its impact on the relationship between procedure time and outcomes. Methods and Results The derivation cohort (n=221) from the ATTENTION (Endovascular Treatment for Acute Basilar Artery Occlusion) study was used. Variables identified by logistic regression were used to develop the Basilar Artery Collateral Simplified Score (BACSS). Its performance was assessed through discrimination and calibration. BACSS was evaluated in an external cohort (n=191). The association between BACSS and outcomes was evaluated using adjusted logistic regression. In patients receiving endovascular treatment, associations of BACSS and time from puncture to recanalization with outcomes were evaluated, including an interaction term (BACSS×puncture to recanalization) to assess effect modification. The primary outcome was 90‐day functional independence (modified Rankin Scale score ≤2). Posterior communicating artery, posterior cerebral artery, and superior cerebellar artery were identified through multivariable logistic regression to establish BACSS. The area under the curve of BACSS was 0.749 (95% CI, 0.679–0.819), comparable to the Basilar Artery on Computed Tomography Angiography score and Posterior Circulation Collateral Score, with substantial interobserver agreement. Both the calibration curves and the Hosmer‐Lemeshow test showed good calibration. Similar findings were observed in the external cohort. BACSS was independently associated with functional independence (adjusted odds ratio, 2.11 [95% CI, 1.53–3.02]). The relationship between puncture to recanalization and outcomes (Pinteraction>0.05) was unchanged. Conclusions BACSS is a simple collateral score with improved interobserver reliability and shows a positive association with outcomes in basilar artery occlusion. In patients with basilar artery occlusion, shorter procedure time during endovascular treatment is associated with favorable outcome, regardless of collateral circulation. Registration URL: https://www.clinicaltrials.gov; Unique Identifier: NCT04751708.